Studi In Vitro dan In Silico EfektivitasEkstrak Mentimun (Cucumis sativus) dalam Menurunkan Hipertensi - Irianto Irianto; Andi Alief Utama Armyn; La Ode Abdul Haris Hijriansyah; Hermilasari Hermilasari; Hardyanty Subair (Nusantara Medical Science Journal, 2020)
Introduction: Hypertension is one of the major causes of stroke. Stroke can be prevented by controlling hypertension. Cucumber proved to have antihypertensive effect. cucumber contains ficetin compounds that play a role in antihypertensives. This study aims to determine the effectiveness of cucumber extract to controlling hypertension. Methods: The research method used is pre-test and post-test matched control group. The 6 wistar rats were divided into 3 groups consisting of 1 treatment groups and 2 control groups. Group P1 was induced by using ketamine 0.05 ml + epinephrine 0.2 ml + 6 ml cucumber extract, group K (-) induced by ketamine 0.05 ml + epinephrine 0.2 ml without extract, and group K (+) induced by using ketamine 0.05 ml + epinephrine 0.2 ml + captopril 2.5 mg Results The results showed that epinephrine can be used as a hypertensive inducer. cucumber extract as much as 6ml can provide antihypertensive effects. In Vitro test result showed that cucumber extract can reduce blood preassure by an average decrease in blood preassure of 102 mmHg While captopril 25,5 mmHg. Conclusions: in addition to the in vitro test, the results of the in silico test showed that the cucumber extract can significantly reduce blood pressure compared to anti-hypertensive drugs (captopril). the value of fisetin in cucumber is -9.3. and captopril only -5.7.Keywords: Hypertension, cucumber extract, In Silico, In Vitro